A case of atypical leiomyoma mimicking as endometrial cancer - Bhadana, Priyanka; Kiran, Abha; Bhakuni, Kriti; Malla, Veena G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Atypical leiomyoma or leiomyoma with bizarre nucleus is diagnosed on histopathological examination characterized by severe cytological atypia in the form of nuclear enlargement, multi nucleation, hyperchromasia, coarse chromatin and prominent nuclei. These tumours do not have typical features of necrosis or mitotic figures to characterize them as leiomyosarcoma. There are 2% risk of these tumours to convert to leiomyosarcoma. 50-year P3L3A1 postmenopausal for past 6 years presented to gynaecology outpatient department (GOPD) with complains of pain in lower abdomen for past 1 year. Patient was examined and investigated. On clinical examination there was no apparent finding. On radiological examination a well-defined hypoechoic lesion of 6.4×5.7 cm2 was found arising from uterus. Contrast enhanced computed tomography (CECT) abdomen showed heterogenous mass involving endometrium and myometrium likely neoplastic. Total abdominal hysterectomy with bilateral salpingoophrectomy was done. Histopathological examination (HPE) report revealed features of atypical leiomyoma. Patient is under follow up in GOPD.